Harnessing Adaptive Urban Service Frameworks and Smart Technologies for Sustainable Urban Development in Rapidly Urbanising Cities - Agboola, Oluwagbemiga Paul; Uzun, Turkan Irgin; Cakir, Hulya Soydas; Soydaş Çakır, Hülya (Elsevier, 2026)
Rapid urbanisation and escalating climate change impacts pose significant challenges for sustainable urban governance in developing nations, particularly where infrastructural inadequacies and resource inefficiencies persist. This study examines how urban systems in rapidly growing cities in Nigeria can utilise smart technologies to enhance resilience, inclusivity, and environmental sustainability. The study's aim is to develop and evaluate an Adaptive Urban Service Framework (AUSF) that integrates digital innovations to foster low-carbon, climate-resilient, and inclusive cities. Objectives of the study include (i) identifying adaptive urban service models that improve resource efficiency, environmental sustainability, and quality of life, and (ii) assessing the extent to which these services strengthen urban resilience and social inclusivity under demographic and infrastructural pressures. A structured survey involving 286 respondents from selected Nigerian cities was conducted, and the data were analysed using SPSS Version 22. The correlation results reveal a positive relationship between adaptive urban service mechanisms and sustainability outcomes (r = 0.987, p < 0.001), indicating that improvements in smart technologies, resource efficiency, environmental sustainability, and quality of life strongly reinforce sustainable urban performance. Similarly, experts' evaluations demonstrate a positive correlation between Adaptive Urban Services (AUS) and the enhancement of resilience and inclusivity within smart urban environments (r = 0.865, p < 0.001). These findings collectively underscore that adaptive, smart-driven frameworks exert substantial synergistic effects on environmental sustainability, social inclusivity, and urban resilience, confirming that the effective integration of smart technologies serves as a strong determinant of sustainability outcomes in rapidly urbanising Nigerian cities. The paper offers a methodology that integrates digital innovation with climate-responsive planning, which theoretically advances urban systems theory. In practical terms, it provides policymakers and urban planners with a scalable road map for implementing adaptive service solutions that connect sustainability, equity, and technology. Overall, within similar emerging urban environments, the study highlights the transformative potential of adaptive urban services in furthering climate adaptation, fostering inclusion, and attaining sustainable urban development.
Keywords: Adaptive Urban Services (AUS); Low-Carbon Cities; Climate Adaptation; Resilient Urban Development; Digital Inclusivity